A JAR of Chirps: The Gymnotiform Chirp Can Function as Both a Communication Signal and a Jamming Avoidance Response - Field, Caitlin E.; Petersen, Thiago Alexandre; Alves-Gomes, José A.; Braun, Christopher B. (Frontiers in Integrative Neuroscience, 2019)
The weakly electric gymnotiform fish produce a rhythmic electric organ discharge (EOD) used for communication and active electrolocation. The EOD frequency is entrained to a medullary pacemaker nucleus. During communication and exploration, this rate can be modulated by a pre-pacemaker network, resulting in specific patterns of rate modulation, including stereotyped communication signals and dynamic interactions with conspecifics known as a Jamming Avoidance Response (JAR). One well-known stereotyped signal is the chirp, a brief upward frequency sweep usually lasting less than 500 ms. The abrupt change in frequency has dramatic effects on phase precession between two signalers. We report here on chirping in Brachyhypopmus cf. sullivani, Microsternarchus cf. bilineatus Lineage C, and Steatogenys cf. elegans during conspecific playback experiments. Microsternarchus also exhibits two behaviors that include chirp-like extreme frequency modulations, EOD interruptions with hushing silence and tumultuous rises, and these are described in terms of receiver impact. These behaviors all have substantial impact on interference caused by conspecifics and may be a component of the JAR in some species. Chirps are widely used in electronic communications systems, sonar, and other man-made active sensing systems. The brevity of the chirp, and the phase disruption it causes, makes chirps effective as attention-grabbing or readiness signals. This conforms to the varied assigned functions across gymnotiforms, including pre-combat aggressive or submissive signals or during courtship and mating. The specific behavioral contexts of chirp expression vary across species, but the physical structure of the chirp makes it extremely salient to conspecifics. Chirps may be expected in a wide range of behavioral contexts where their function depends on being noticeable and salient. Further, in pulse gymnotiforms, the chirp is well structured to comprise a robust jamming signal to a conspecific receiver if specifically timed to the receiver’s EOD cycle. Microsternarchus and Steatogenys exploit this feature and include chirps in dynamic jamming avoidance behaviors. This may be an evolutionary re-use of a circuitry for a specific signal in another context.